If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(a + -4b) + -2(a + 4b) = 0 (a * 3 + -4b * 3) + -2(a + 4b) = 0 (3a + -12b) + -2(a + 4b) = 0 3a + -12b + (a * -2 + 4b * -2) = 0 3a + -12b + (-2a + -8b) = 0 Reorder the terms: 3a + -2a + -12b + -8b = 0 Combine like terms: 3a + -2a = 1a 1a + -12b + -8b = 0 Combine like terms: -12b + -8b = -20b 1a + -20b = 0 Solving 1a + -20b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '20b' to each side of the equation. 1a + -20b + 20b = 0 + 20b Combine like terms: -20b + 20b = 0 1a + 0 = 0 + 20b 1a = 0 + 20b Remove the zero: 1a = 20b Divide each side by '1'. a = 20b Simplifying a = 20b
| -5(-4+2x)=-10 | | 6-2u=-4 | | 3x+9y=32 | | 9x-9=-63 | | -8x+7x-9x-x= | | 20(v+3)-4v=4(4v+1)-10 | | 6x-1=-5x+10 | | -5(-4+2x)=10 | | C=mv-mu | | 20-4x=8-4(x-3) | | 11x-(5x-5)=47 | | 0.5x-1.3=-8.8 | | 3(4x-2)=10x+10 | | 4(5-x)+3=20 | | -5(1x+9)=-20 | | 2(p-4)=12 | | 6x+30=3x-3 | | 5(4a+2b)-3(2a+b)= | | 2x=180-80 | | -3.8T+4=4.4T-3 | | 6x+147=16x-13 | | 13a-8+4=11 | | 13a-81+4=11 | | 2x=180-76 | | 3(x+4)+8=5x+2 | | y=20x+34 | | 6x-7=x+5 | | 3(x-11)=10-4x | | 25-2yz= | | -5x+2=7x-16 | | 9x+1=4x-10 | | (x+10)(x+10)(x-10)(x-10)= |